2004
DOI: 10.1126/science.1102941
|View full text |Cite
|
Sign up to set email alerts
|

By Carrot or by Stick: Cognitive Reinforcement Learning in Parkinsonism

Abstract: To what extent do we learn from the positive versus negative outcomes of our decisions? The neuromodulator dopamine plays a key role in these reinforcement learning processes. Patients with Parkinson's disease, who have depleted dopamine in the basal ganglia, are impaired in tasks that require learning from trial and error. Here we show, using two cognitive procedural learning tasks, that Parkinson's patients off medication are better at learning to avoid choices that lead to negative outcomes than they are at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

176
2,142
29
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,790 publications
(2,357 citation statements)
references
References 34 publications
176
2,142
29
10
Order By: Relevance
“…In particular, studies in patients with severe PD, accompanied by DA loss in the NAc, will reveal whether or not the L-DOPA-induced deficit in mild PD depends on the level of DA depletion in the NAc. Whereas other accounts of the medication-induced impairment do not require the NAc to be intact (Frank et al, 2004), we predict that the impairment is abolished with progression of the disease.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In particular, studies in patients with severe PD, accompanied by DA loss in the NAc, will reveal whether or not the L-DOPA-induced deficit in mild PD depends on the level of DA depletion in the NAc. Whereas other accounts of the medication-induced impairment do not require the NAc to be intact (Frank et al, 2004), we predict that the impairment is abolished with progression of the disease.…”
Section: Discussioncontrasting
confidence: 65%
“…In keeping with this prediction, the present observation confirms that L-DOPA interacts with the NAc, not the dorsal striatum during reversal learning. One mechanism by which L-DOPA may 'over-dose' reversal learning was proposed by Frank et al (2004). These authors suggested that L-DOPA-induced increases in tonic DA may 'fill in' phasic DA dips, thought to accompany omissions of reward (Hollerman and Schultz, 1998), thereby attenuating reward-prediction error signals.…”
Section: Discussionmentioning
confidence: 99%
“…Here we report simulations with a simplified and generalized version of the probabilistic selection task (Frank, Moustafa, et al, 2007;Frank et al, 2004; see Figure 3), but the same results hold with the empirical version of the task.…”
Section: Probabilistic Selection Taskmentioning
confidence: 70%
“…Without the multiplicative update, G and N weights evolve symmetrically, with no preferential differentiation among positive or negative values, and as such are linear combinations of true expected value, leading to equal Choose-A and Avoid-B performance (see Appendix, supplemental simulations in Figure A2). Dopaminergic manipulations in the probabilistic selection task have been shown repeatedly (Frank, Moustafa, et al, 2007;Frank & O'Reilly, 2006;Frank et al, 2004;Jocham et al, 2011;Shiner et al, 2012;Smittenaar et al, 2012) to induce changes in Choose-A versus Avoid-B bias, although it has not been clearly disentangled whether this was due to learning effects or performance effects. As noted earlier, some studies show effects of dopamine medication in which Choose-A performance is improved even when the design was such that medications could have only affected test performance rather than learning (Shiner et al, 2012;Smittenaar et al, 2012).…”
mentioning
confidence: 99%
“…It is not clear whether the reduction seen in addiction is mainly pre-or postsynaptic, but both could potentially promote drug-taking. Postsynaptically, they have been shown to mediate the effect of losses on "go/no-go" learning (Frank, 2005;Frank et al, 2004;Dreyer et al, 2010;Kravitz et al, 2012), and could thereby contribute to the insensitivity towards adverse consequences in addiction (Vanderschuren and Everitt, 2004;Deroche-Gamonet et al, 2004;Maia and Frank, 2011;Kravitz et al, 2012). Presynaptically, they are involved in an autoinhibitory negative feedback loop which could particularly affect go-learning as it could reduce the positive phasic transients (Bello et al, 2011) and thereby lead to the sort of increased prediction error increase mentioned above (Bello et al 2011; see also Sulzer 2011).…”
Section: Phasic Dopaminergic Signals In Addictionmentioning
confidence: 99%